A legal study on the need to legislate third parties rights in contracts in Malaysia / Nur Sulehan Abd Rahman, Nur Atiqah Abu Zahar and Nurul Ain Syazwi Harun - Abd Rahman, Nur Sulehan; Abu Zahar, Nur Atiqah; Harun, Nurul Ain Syazwi (2011)
The Doctrine of Privity provides that a thifd party cannot confef rights of impose obligations arising under the contract though the contracts were made for his benefit. Thus the archaic doctrine of privity had cause so many difficulties and defectiveness notwithstanding the existing exception applied to circumvent the rule of privity. There is a need for research to be conducted to the understanding in relation to the extent of the application of law pertaining to the doctrine of privity in Malaysia. As United Kingdom has enacted an Act to recognize the rights of third party, a comparative study of Malaysia and United Kingdom is conducted to compare the application of laws from both countries in this specific area.